Fully automated analysis approach for in situ electron diffraction - Lim, Sooyeon; Park, Soohyung; Kim, Hong-Kyu; Choi, In-Chan (The Korean Physical Society, 2024)
Despite the rapid development of the state-of-the-art in-situ/operando transmission electron microscopy technologies capable of generating a substantial volume of diffraction pattern images in a compressed time frame, the associated image interpretation apparatus remains incompletely automated. Since the analysis of the acquired data is predominantly focused on a subset of this extensive data set, there is the potential for critical information to be inadvertently omitted. Using a set of computer vision algorithms, we have developed a fully automated computational tool specifically tailored for the systematic analysis of electron diffraction patterns. Our research results demonstrate that the proposed methodology represents a viable and effective approach for the automated analysis of the substantial corpus of data collected during in-situ experimental investigations.